Training on Virgin Coconut Oil (VCO) Production with Temperature Control in The Mekar Makmur Women Farming Group of Ngadipuro Village, Blitar - Yudaningtyas, Erni; Nurdiana; Zakiyah Amalia (Fakultas Teknik, Universitas Brawijaya, 2026)
The Mekar Makmur Women Farmers Group (KWT) in Ngadipuro Village, Wonotirto District, Blitar Regency, has abundant local coconut potential, but its utilization is still limited to household consumption. In fact, coconut derivative products such as Virgin Coconut Oil (VCO) have high added value both economically and health-wise. The community service method is implemented through identification, socialization, technical training on VCO production with a controlled temperature chamber, business management training, and marketing assistance. To support the sustainability of the program, the team also handed over three temperature-controlled chambers and one stainless steel hydraulic coconut milk press to the KWT. ​​The results of the activity showed an increase in members' skills in operating the chamber, the production of a minimum of 5 liters of VCO with better quality according to fatty acid content tests, and the formation of a pilot VCO business unit. The appropriate technology provided has been proven to speed up the extraction process, improve hygiene, and produce clear, long-lasting VCO rich in medium-chain fatty acids. This activity has implications for strengthening the role of women in entrepreneurship based on local potential.